(untitled) (Global Journal of Science Frontier Research, 2013)
The relationships between Laplace and Fourier transformations are studied very closely. It is observed that Fourier transformation can be obtained from Laplace transformation but the reverse is not true. Based on this, a generic mathematical analysis leads to an expression relating Laplace transformation to Fourier transformation. Further mathematical analysis from that expression leads to something quite new: The Discrete Version of Laplace transformation, which the author calls sigma (σ) transformation.